Exposure to violence within home and community environments and psychopathic tendencies in detained adolescents - Schraft, Cody V. (Criminal justice and behavior, 2013)
Prior studies have reported correlations between childhood abuse and antisocial behavior and psychopathy, which suggest that exposure to violence may be a risk factor for the development of psychopathy. However, prior studies are largely limited to retrospective studies of adult samples and studies of violence within the home environment. To increase our understanding of risk factors relevant to the development of psychopathy, we investigated associations between self-reports of exposure to violence within the home and community and psychopathic traits in adolescents. A total of 147 adolescents at an Illinois detention center completed the Childhood Trauma Questionnaire (CTQ) and Community Experience Questionnaire (CEQ) and were assessed using the Psychopathy Checklist: Youth Version (PCL:YV). CEQ and CTQ total scores were associated with psychopathy scores. Moreover, exposure to violence within the community correlated uniquely with scores on the interpersonal, behavioral, and antisocial factor of psychopathy, and exposure to home violence was uniquely related to behavioral factor scores. Results highlight the potential contribution of environmental factors to core components of psychopathy.